2018
DOI: 10.25258/ijpqa.v9i2.13646
|View full text |Cite
|
Sign up to set email alerts
|

Study of Catsper1 Protein Levels in Unexplained and Idiopathic Infertile Men

Abstract: Catsper 1 is an important protein involved in calcium channel synthesis. These channels are essential for the hyperactivity of sperm flagellum, chemotaxis towards the egg, capacitation and acrosome reaction. Data analysis from unexplained infertility (n=50), idiopathic infertile men (Asthenozoospermia (n=50), Oligozoospermia (n=50)), and Normospermia fertile men as a control (n=26). The expression of CatSper1 protein expression in spermatozoa was reduced in unexplained infertility (mean± SD. Error 64.32±2.5 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…The current study also showed a positive correlation between the level of interleukin-10 and WBC and perhaps the reason for this is that the increase in the level of white blood cells during pregnancy or spontaneous miscarriage in women, which is often accompanied by an increase in urinary and genital tract infections which leads to an increase in the level of interleukin -10 (15,16) .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The current study also showed a positive correlation between the level of interleukin-10 and WBC and perhaps the reason for this is that the increase in the level of white blood cells during pregnancy or spontaneous miscarriage in women, which is often accompanied by an increase in urinary and genital tract infections which leads to an increase in the level of interleukin -10 (15,16) .…”
Section: Discussionsupporting
confidence: 70%
“…In vitro fertilization , intracytoplasmic sperm injection (ICSI) , and intrauterine insemination (IUI) be are the main methods of assisted reproductive technology (ART). Found several Various studies in recent years have indicated that occur risk factor for implantation failure of women after In vitro fertilization -ICSI which may be immunological parameters or biochemical parameters may be affected on In vitro fertilizationintracytoplasmic sperm injection results (15) . White blood cells (WBCs) They are considered an important part of the immune system in the body ,It should be noted that the increase in the number of white blood cells or their lack of a normal limit indicates the presence of a health problem that afflicts the patient, he cause of white blood cells rise for a number of reasons, the most important of which are summarized below For pregnancy and childbirth or spontaneous miscarriage because increase Infection in Urinary tract with or immune system problem (2,16) .…”
Section: Introductionmentioning
confidence: 99%
“…The most successful fertility in pets. Also, fertility is a success against sperm DNA damage (1) . Thioredoxin family proteins It participates in an antioxidant system and is one of various groups, as it has a role in cellular functions, There are three thioredoxins It is especially expressed in male mammals (2,3) .…”
Section: Introductionmentioning
confidence: 99%
“…The most important source of vitamin D is the skin's synthesis of vitamin B from ultraviolet B, and any process that reduces the entry of ultraviolet B photons into the skin will reduce the production of cholecalciferol (vitamin D-3). Melanin absorbs skin pigment with UVB photons and can reduce vitamin D-3 synthesis by> 90% 10,11 .Vitamin D also worsens in the winter months (November to March), when latitudes reach above 37 °C ultraviolet B radiation decreases to Earth and little or no vitamin D can be synthesized in the skin, as vitamin D plays a prominent role in Calcium and phosphorous stabilization, and its deficiency has been shown to increase the risk of osteoporosis, fractures, and muscle weakness 12,13 . Also, female reproduction is a one of the areas in which the role of vitamin D has not been extensively examined.…”
Section: Introductionmentioning
confidence: 99%
“…However, early evidence from basic research strongly indicates the potential role of vitamin D in human reproduction, especially women 14,15 . It turns out that the effects of a lack of Vitamin D3 on pregnant women expose them to the problems of spontaneous abortion or premature birth due to failure of the placenta function, pre-eclampsia, gestational diabetes, bacterial vaginitis, and poor growth and development of the fetus and childhood, as preserving must be maintained at sufficient levels throughout the period Pregnancy 16,17 . The aim of this study was to study the relationship of white blood cell count in pregnancy and its relationship to vitamin D3 for aborted women under ICSI.…”
Section: Introductionmentioning
confidence: 99%